2021
DOI: 10.1016/j.cmi.2021.05.020
|View full text |Cite
|
Sign up to set email alerts
|

An open-label randomized controlled trial of the effect of lopinavir/ritonavir, lopinavir/ritonavir plus IFN-β-1a and hydroxychloroquine in hospitalized patients with COVID-19

Abstract: C, Mentre F, on behalf of the DisCoVeRy study group, An open-label randomized, controlled trial of the effect of lopinavir/ritonavir, lopinavir/ritonavir plus IFN-β-1a and hydroxychloroquine in hospitalized patients with Clinical Microbiology and Infection,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 29 publications
2
77
0
Order By: Relevance
“…The hospital discharge rate was reported in 65 studies including 53,636 patients and 34,247 events. Treatment nodes included in the network were azithromycin, bamlanivimab, baricitinib plus remdesivir, camostat mesilate, canakinumab, convalescent plasma, dapagliflozin, dexamethasone, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, interferon beta, ivermectin, lopinavir/ritonavir, mesenchymal stem cells, remdesivir, sarilumab, tocilizumab, tofacitinib and SOC, which were investigated in 48 studies ( 3 , 6 , 22 26 , 31 , 43 , 46 , 55 , 57 , 64 , 71 73 , 76 , 80 , 82 , 84 , 89 , 91 , 93 , 96 98 , 100 , 101 , 106 , 107 , 109 , 110 , 115 , 116 , 121 , 122 , 124 , 126 , 128 132 , 145 147 , 157 , 158 ). Out of the 48 studies included in the NMA, 19 were evaluated as low risk ( Supplementary Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hospital discharge rate was reported in 65 studies including 53,636 patients and 34,247 events. Treatment nodes included in the network were azithromycin, bamlanivimab, baricitinib plus remdesivir, camostat mesilate, canakinumab, convalescent plasma, dapagliflozin, dexamethasone, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, interferon beta, ivermectin, lopinavir/ritonavir, mesenchymal stem cells, remdesivir, sarilumab, tocilizumab, tofacitinib and SOC, which were investigated in 48 studies ( 3 , 6 , 22 26 , 31 , 43 , 46 , 55 , 57 , 64 , 71 73 , 76 , 80 , 82 , 84 , 89 , 91 , 93 , 96 98 , 100 , 101 , 106 , 107 , 109 , 110 , 115 , 116 , 121 , 122 , 124 , 126 , 128 132 , 145 147 , 157 , 158 ). Out of the 48 studies included in the NMA, 19 were evaluated as low risk ( Supplementary Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 45 studies including 6,631 patients reported viral clearance rates and after eliminating treatments with inadequate numbers of patients, 32 studies were considered in the NMA ( 36 , 53 , 54 , 56 , 57 , 59 , 65 , 68 , 71 , 72 , 76 , 78 , 80 , 91 , 106 , 109 , 119 , 132 , 136 , 137 , 141 , 153 , 157 166 ), of which 10 were assessed as low risk ( Supplementary Table 8 ). Treatment nodes in the network included bamlanivimab, bamlanivimab plus etesevimab, convalescent plasma, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, ivermectin, ivermectin plus doxycycline, lopinavir/ritonavir, methylprednisolone, nitazoxanide, proxalutamide, remdesivir and SOC.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven new RCTs were retrieved by the SLR search update, adding to the existing eight RCTs on HCQ included in the previous SLR. Out of these 11 new studies, 4 have been stopped early for futility, 4–7 2 have been stopped for harmful effects of one or several compounds in the intervention arms, 8 9 and 1 is underpowered, 10 hence the results are not described in this manuscript. Out of the six studies that included patients with moderate to severe COVID-19, one compared HCQ to chloroquine or ivermectine showing no efficacy on death, progression to invasive mechanical ventilation (IMV) or admission to intensive care unit (ICU) at day 90.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were randomly assigned 1:1:1:1:1 when five groups were initially implemented, and were then assigned 1:1 to receive either standard of care or standard of care plus remdesivir, once the other three treatment groups had been stopped for futility. 2 Participants allocated to standard of care alone or in combination with remdesivir were recruited contemporaneously.…”
Section: Randomisation and Maskingmentioning
confidence: 99%
“…1 Results for lopinavir-ritonavir, lopinavirritonavir plus interferon beta-1a, and hydroxychloroquine have been reported elsewhere. 2 Remdesivir is a small molecule that is formulated with sulfobutylether B-cyclodextrin sodium for injection, is dialysable, is known to penetrate well into deep compartments, and is devoid of drug interactions via CYP450. 3,4 Remdesivir is a nucleotide analogue prodrug that is intracellularly metabolised to an analogue of ATP, which inhibits RNA polymerase activity in some pathogenic coronaviruses.…”
Section: Introductionmentioning
confidence: 99%